Broadband phase shifters using comprehensive compensation method. Issue 4 (April 2017) - Peng, Hao; Xia, Xinlin; Ovidiu Tatu, Serioja; Xu, Kai‐Da; Dong, Jun; Yang, Tao
ABSTRACT: In this letter, broadband phase shifters using comprehensive compensation method have been presented. The phase shift is dependent on the differences of substrate integrated waveguide (SIW) width, SIW length, microstrip‐line length, and permittivity. The overall phase shift can be compensated mutually due to different physical parameters of constitutive transmission lines, as explained in details in this letter. The fillers with different dielectric permittivity are filled in the SIW's interior with a metalized PCB closely covered on the surfaces. Measurement results show that the fractional bandwidths for 45.1° ± 3° and 90° ± 5.1° versions can be up to 70.4% and 69%, respectively. For the operating frequency band, the return losses are all better than 13.5 dB, and the insertion losses are all less than 1.7 dB. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:766–770, 2017